Evaluación de la intensidad de campo electromagnético producido por antenas de telecomunicaciones en la ciudad de Calceta - Molina Huerta, Luis Fernando (2020)
The exponential growth of telephone base stations within cities has triggered the inhabitants' concern about the possible health effects that non-ionizing radiation produces. For this reason, the electromagnetic field intensity produced by telecommunication antennas in Calceta city was evaluated. For the measurements of the variables, the TM-195 equipment was used, taking data on the X, Y and Z axes at strategic points in Calceta city, georeferenced by means of a GPS, obtaining as a result of an electromagnetic field an average of 0.0167 W / m2 which represents 0.03% of the limit recommended by CONATEL, being 48.75 W / m2 for occupational exposure and 9.75 W / m2 for population exposure, thus demonstrating that radiation does not exceed the recommended limits. An incidence map was made which determined that the central area of Calceta city is the most irradiated by the electromagnetic field due to the close positioning of 7 telecommunications antennas. A population survey was also applied, which determined that 83% of the respondents remain in occupational exposure and although 87% of the study population is aware of the presence of antennas, 29% of them believe that the Non-ionizing radiation has carcinogenic health effects, which shows that they are unaware of the subject in question.